STUDI PRAKTIKA TEOLOGIS TENTANG PENTINGNYA INTEGRITAS HAMBA TUHAN DALAM MEMENUHI PANGGILAN BERDASARKAN 2 KORINTUS 11:7-33 BAGI MAHASISWA SEKOLAH TINGGI TEOLOGI - Natanaeli Waruwu; Subagio Wirdjo Mintodihardjo (Sekolah Tinggi Teologi Duta Panisal, 2022)
The research in this thesis is motivated by the lack of integrity of the servant of God for Duta Panisal Theology College Students, which affects the personality formation of a servant of God. Therefore, researchers can apply the importance of integrity in God's servants for students during the character building period in the institute environment to support the future of God's servants with integrity, because integrity is a quality of life that has commitment and a firm stance in serving. The researcher uses a qualitative approach which is an effort made by researchers in understanding, researching, observing and implementing solutions to problems that occur in the field. The method of data collection researchers used a structured interview method with statements. This process the researchers did to obtain information and data in the field through interviews, documentation, and literature studies that were compiled and drawn conclusions. In self-integrity, a servant of God must possess humility, not trouble others, dare to fight false teachings, make sacrifices, and care for the congregation. It has been established and understood that integrity is very important as a quality and a living sermon so that it can realize the positive values that are instilled in the lives of God's servants in service. This is very useful for Duta Panisal Theological College students in improving the integrity of God's servants within themselves in the institute environment in order to prepare themselves to become servants of God with integrity.